Exit Survey Kepuasan Wisatawan Terhadap Pariwisata di Labuan Bajo - Marselina, Apriana; Leha, Ernesta; Ota, Maria Kristina (Jurnal Master Pariwisata (JUMPA); Volume 06, Nomor 02, Januari 2020DO - 10.24843/JUMPA.2020.v06.i02.p08, 2020)
Tourism is one of the important sectors as a source of regional income. The satisfaction of each tourist depends on the facilities and services provided. The purpose of this survey is to measure the satisfaction of tourists who come and visit tourist destinations in Labuan Bajo. This survey activity also measures the success of the West Manggarai Regional Government, all stakeholders and the community in maintaining the sustainability of tourism in Labuan Bajo, as well as being able to answer user needs based on user experience. This survey was conducted using the exit survey method, by interviewing as many tourists as possible who had visited Labuan Bajo and were going out through the existing airport in Labuan Bajo. Based on the results of research on the level of visitor satisfaction with services and facilities in several tourist destinations in Labuan Bajo are between 55.28% to 76.45% of tourists satisfied with the existing facilities and services. This research contributes to the government of West Manggarai Regency in increasing the number of tourist visits and the development of facilities and services for tourists for each tourist destination in West Manggarai. Keywords: Exit Survey, Tourist Satisfaction, Sustainable Tourism